Fluoroscence bronhoscopy - Tomić Ilija; Mrđa Vladimir; Karličić Vukojica; Bokun Radojka; Tatomirović Željka (Vojnosanitetski Pregled)
Background. Fluorescence bronchoscopy is one of the methods of the early detection of lung cancer that involves the large airways. The method is based on the detection of the altered autofluorescence of malignantly transformed tissue, and confirmed by biopsy and histopathologic examination. Method. Fluorescence bronchoscopy was performed in 18 patients, mean age of 51.2 years (male n=12, female n=6) due to the suspected lung cancer. Fluorescence bronchoscopy was performed using the Xillix LIFE-Lung System Vancouver, Canada. After conventional white-light bronchoscopy, the tracheobronchial tree was illuminated by blue light (442 nm) using helium-cadmium laser, and the results of autofluorescence were classified into three classes. Normal mucosa was of green fluorescence (Class I) abnormal mucosa was red or dark brown fluorescence (Class II and II), which was the indication for performing biopsy. Results. Normal endoscopy findings were established in 15 patients by conventional bronchoscopy. In the same group, by fluorescence bronchoscopy, Class I of fluorescence (normal finding) was found in 9 patients, while Class II changes occured in 6 patients. Histopathologic analysis of bronchial mucosa with Class II changes was performed detecting planocellular carcinoma in situ in one patient. Tumor-like changes were detected in 3 patients by conventional bronchoscopy and were determined as Class III changes by fluorescence bronchoscopy. By the biopsy of these chages carcinoma was documented in 2 patients while in one patient metaplasia of epithelium and granulation tissue around aspirated foreign body was detected. Conclusion. Fluorescence bronchoscopy is one of the methods for detecting metaplasia, carcinoma in situ and cancerous changes of bronchial epithelium in the large airways. However, the high rate of falsely positive findings represents a limitation of this method.